Three New Deir el-Medina Absence Lists in the Ashmolean Museum, Oxford - Hudson, Stephanie E. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
This article presents three previously unpublished hieratic absence lists in the Ashmolean Museum, Oxford: Ashmolean HO 563, Ashmolean HO 679, and Ashmolean HO 808. The ostraca date to the Nineteenth and Twentieth Dynasties and are identifiable as originating from the records of the Deir el-Medina workmen’s community. The texts record workmen’s names with reasons for absence from work on the royal tomb for particular days. Both individual and collective absence is expressed, using administrative phraseology attested in previously published absence documents. The ostraca are unprovenanced; however, the subject matter of the texts is suggestive of a worksite derivation. Moreover, the prosopographical data and content of one of the group, Ashmolean HO 808, makes it likely that it came originally from the Valley of the Kings.